SYNTHESIS AND CATALYTIC PROPERTIES OF COMPOSITES WITH Pd-(2-HYDROXYETHYL CELLULOSE) ON BENTONITE - A.K. Zharmagambetova,; M.M. Usmanova,; A.S. Auyezkhanova,; Akhmetova S.N.,; E.T. Talgatov ,; Tumabayev N.Z.,; B.K. Dyussenalin, (Academic Scientific Journal of Chemistry, 2019)
Palladium composites based on 2-hydroxyethylcellulose (HEC) and bentonite (BT) have been synthesized to use them as “green” catalysts for the process of phenylacetylene hydrogenation under mild conditions. The introduced amount of HEC in the composites was 5, 10, and 20%. Viscometer method shows the degree of polymer fixation on the surface of the mineral sorbent. The HEC/BT systems with polymer content of 4.1; 9.0; 18.9% have been obtained. Samples of the obtained HEC-containing composites were characterized by X-ray, scanning and transmission electron microscopy. The data obtained have confirmed the fixing of the polymer on the surface of support. The sorption capacity of the developed HEC-bentonite composites to Pd2+ ions has been studied. The content of palladium in the prepared composites desreased with the increasing of HEC amount in the [Pd(HEC)BT] systems and were : 0.9% Pd-BT/HEC (4%), 0.8% Pd-BT / HEC (9%), 0.6% Pd-BT / HEC (19%). To compare the activity and selectivity of composites with different content of HEC in phenylacetylene hydrogenation, the catalysts with the equal palladium content (0.6%) have were prepared. The developed catalysts showed high activity in the hydrogenation at 40°C and atmospheric pressure of hydrogen. The most effective was 0.6% Pd-BT/HEC composite with a HEC content of 9%, the selectivity to styrene was 92.0% with 96.4% conversion of the phenylacetylene.